2022
DOI: 10.1186/s12872-021-02401-y
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates myocardial fibrosis by regulating Sirt1/Smad3 deacetylation pathway in rat model with dilated cardiomyopathy

Abstract: Background The aim of this study was to investigate the effects of Resveratrol (RSV) in rats with dilated cardiomyopathy (DCM). Methods Porcine cardiac myosin was used to set up rat model with DCM. RSV (10 mg/kg in RSV-L group and 50 mg/kg in RSV-H group) or vehicle was administered to rats with DCM once daily from the 28th day till the 90th day after the first immunization. Cardiac function of rats was evaluated by echocardiographic analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…As previously reported, the SIRT1 signaling pathway is involved in the regulation of autophagy and apoptosis and has been studied as part of the mechanism of resveratrol in various diseases (Chen et al, 2022;Gomes et al, 2018;Nishigaki et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As previously reported, the SIRT1 signaling pathway is involved in the regulation of autophagy and apoptosis and has been studied as part of the mechanism of resveratrol in various diseases (Chen et al, 2022;Gomes et al, 2018;Nishigaki et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…SIRT1 is a member of the class III histone deacetylase family that is distinctively dependent on nicotinamide adenine dinucleotide (NAD+) for catalytic reactions (Yousafzai, Jin, Ullah, & Wang, 2021); SIRT1 modulates gene expression, apoptosis, energy homeostasis, autophagy, acute stress responses, and mitochondrial biogenesis (Tovar‐Palacio, Noriega, & Mercado, 2022). Resveratrol is an agonist of SIRT1, so the activation of SIRT1 signaling is considered a key mechanism for its effects on a variety of diseases (Chen et al, 2022; Gomes et al, 2018; Nishigaki, Tsubokura, Tsuzuki‐Nakao, & Okada, 2022). Additionally, studies have also shown that the JNK pathway is a potential target of resveratrol (Shati, 2019; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this model, KAT2B induces acetylation of SMAD2 and, subsequently, activates SMAD2 and the transforming growth factor β signaling pathway [ 39 ]. SMAD3 could also be acetylated during cardiac fibrosis [ 41 , 42 ]. Activation of SIRT1 by resveratrol [ 41 ], nicotinamide mononucleotide [ 42 ] or geniposide [ 70 ] could decrease SMAD3 acetylation and fibrosis.…”
Section: Implication Of Cardiac Acetylation In Metabolic Heart Diseasementioning
confidence: 99%
“…SMAD3 could also be acetylated during cardiac fibrosis [ 41 , 42 ]. Activation of SIRT1 by resveratrol [ 41 ], nicotinamide mononucleotide [ 42 ] or geniposide [ 70 ] could decrease SMAD3 acetylation and fibrosis. Moreover, inhibition of P300 appears to exert anti-fibrotic functions [ 82 ].…”
Section: Implication Of Cardiac Acetylation In Metabolic Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation